Al Azhar Alumni’s Contribution to The Study of The Qur’an in Indonesia: Case Analysis of The Translation of Muhammad A. Khalafullah’s Work - Anwar, Muhammad Khoirul (Proceedings of International Conference on Muslim Society and Thought, 2024)
Abstract: The return of Indonesian students from Al-Azhar University, Egypt has made a major contribution to the dynamics of Islamic scholarship, including through translation activities of the works of Al-Azhar scholars. This activity is motivated by the motivation to transmit Al-Azhar knowledge which is considered to have the opportunity to be introduced to readers in Indonesia. Ahmad Khalafullah’s work is one of the thoughts of Al-Azhar scholars that received this attention. Through qualitative methods involving literature review, this article explains this phenomenon as the dynamics of Quranic studies. Then an analysis was carried out using Kuntowijoyo’s theory of intellectual history which was seen from three aspects, namely: text, context and influence of thought. This article concludes that the translation of Ahmad Khalafullah’s work in the field of Quranic studies is considered by the translator to have an important contribution to the post-reform Indonesian context, where the floodgates of thought are wide open. The influence of the translation of Ahmad Khalafullah’s work has had an impact on the development of thought in Indonesia within the framework of a progressive thought project in the study of the Al-Qur’an as well as being used as a research object.